2015
DOI: 10.1080/21606099.2015.1047473
|View full text |Cite
|
Sign up to set email alerts
|

Deep-red electrophosphorescence from a platinum(II)–porphyrin complex copolymerised with polyfluorene for efficient energy transfer and triplet harvesting

Abstract: A series of polyfluorene-based polymers with a range of weight percentages (w/w) of a platinum(II)-containing porphyrin, 5,15-dimesityl-10,20-diphenylporphyrinato platinum(II) (MPP(Pt)), were synthesised and incorporated into organic lightemitting diodes. All polymers showed emission predominantly in the red/NIR region with only those polymers with porphyrin w/w of less than 2% showing residual tails at wavelengths lower than 600 nm, indicating increased emission from the porphyrin as w/w increases. The 2% loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…20 Please note that the EQE of NIR OLEDs is generally much lower than that of OLEDs emit-ting in the visible range. [17][18][19][20][21]47,52 This is a result of different factors and in particular of the so-called "energy-gap law" (vide infra), and possibly of an increased tendency towards the formation of H-aggregates, owing to a more spatially extended conjugation. H aggregates act as traps for excitons because of their lower energy compared to the unaggregated species, but emit with lower efficiency due to a vanishing dipole moment in the excited states, as clearly demonstrated by comparison of conjugated analogues in which aggregation is impeded by supramolecular engineering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Please note that the EQE of NIR OLEDs is generally much lower than that of OLEDs emit-ting in the visible range. [17][18][19][20][21]47,52 This is a result of different factors and in particular of the so-called "energy-gap law" (vide infra), and possibly of an increased tendency towards the formation of H-aggregates, owing to a more spatially extended conjugation. H aggregates act as traps for excitons because of their lower energy compared to the unaggregated species, but emit with lower efficiency due to a vanishing dipole moment in the excited states, as clearly demonstrated by comparison of conjugated analogues in which aggregation is impeded by supramolecular engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work within the group has shown the utility of a platinum(II) complexed porphyrin (MPP(Pt)) covalently bonded in a fluorene polymer backbone. 17 The calculated energy levels of MPP(Pt) are also shown in Fig. 1.…”
Section: Designmentioning
confidence: 96%
See 1 more Smart Citation
“…16 After this report, it was found that porphyrin derivatives can be integrated as NIR emitters in fluorescent and phosphorescent OLEDs due to their intense absorption and emission in the red-to-NIR region. [17][18][19][20][21][22][23][24][25][26] Porphyrins, consisting of four pyrrole rings interconnected by ethylene groups and (usually) a central metal ion kept in the center by the correlation bonds with the four N atoms, are highly stable to light, heat, and O 2 , and possess excellent fluorescence in solution due to their robust and planar structure. 11 Moreover, the photophysical properties of porphyrin can be modified by changing substituents or central metal ions.…”
Section: Porphyrin-based Nir Fluorescent Materialsmentioning
confidence: 99%
“…By varying the loading of M11 (0.5%, 1%, 2%, and 5%), the PLEDs incorporating these copolymers as a neat emitting layer showed EL peaks at 665, 736, and 818 nm with a shoulder peak at 642 nm and EQEs ranging from 0.17% to 0.48%. 26 In 2016, the same group reported a PLED incorporating M11 copolymerized with poly(diphenylanthracene) as an emitting layer. The device with 10% porphyrin loading showed an EL peak at 760 nm and an EQE up to 0.03%, revealing a remarkable redshift compared to its PL peak at 666 nm.…”
Section: Pt-based Phosphorescent Materialsmentioning
confidence: 99%